2016
DOI: 10.2337/db16-0212
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Insulin and IGF-1 Receptors in Adipose Tissue Development and Function

Abstract: To determine the roles of insulin and insulin-like growth factor 1 (IGF-1) action in adipose tissue, we created mice lacking the insulin receptor (IR), IGF-1 receptor (IGF1R), or both using Cre-recombinase driven by the adiponectin promoter. Mice lacking IGF1R only (F-IGFRKO) had a ∼25% reduction in white adipose tissue (WAT) and brown adipose tissue (BAT), whereas mice lacking both IR and IGF1R (F-IR/IGFRKO) showed an almost complete absence of WAT and BAT. Interestingly, mice lacking only the IR (F-IRKO) had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
113
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 42 publications
5
113
0
Order By: Relevance
“…functions (6,(29)(30)(31)(32). Recent studies have shown that the brain is a major target of insulin/IGF-1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…functions (6,(29)(30)(31)(32). Recent studies have shown that the brain is a major target of insulin/IGF-1 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, deletion of insulin receptors in UCP1 + brown/beige adipocytes also decreases BAT mass (104). Deletion of insulin receptors in adiponectin + adipocytes (white, brown, and beige adipocytes) also decreases BAT mass and impairs cold adaptive thermogenesis in mice (30). These genetic data suggest that insulin signaling is required not only for brown adipogenesis and BAT development but also for the maintenance of the thermogenic and metabolic phenotypes of BAT, and perhaps also beige fat.…”
Section: Humoral Regulation Of Brown and Beige Fat Thermogenesismentioning
confidence: 99%
“…However, elevated circulating insulin levels have been reported prior to the onset of obesity (3,4), and increasing evidence suggests that hyperinsulinemia is not simply an adaptive response to obesity (5). In support of this concept, adipose tissue-specific impairment of insulin signaling prevents obesity in mice (6)(7)(8)(9)(10). Furthermore, we recently reported that mice with lifelong prevention of diet-induced hyperinsulinemia by partial insulin gene deletion were protected against high-fat diet (HFD)induced obesity (11,12).…”
mentioning
confidence: 95%